Career development pathways for gender scientists leadership and mentoring program: Roadmap and action plan - African Women in Agricultural Research and Development; CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
The GENDER Platform through its capacity-development strategy has established the need to prioritize and foster the practice of gender integration throughout the agricultural research for development (AR4D) portfolio of projects and interventions. Agricultural scientists, managers and particularly gender researchers are at the core of these processes to ensure effective and appropriate responses to the needs and priorities of diverse groups of food system actors—including their most marginalized members, such as rural women. This means making realities and experiences of differentiated groups, an integral part of the design, implementation, monitoring and evaluation of all AR4D work, so that all are represented equitably and benefit equally. To achieve this, gender researchers, working across AR4D institutes and embedded within multi-disciplinary teams, should be equipped to lead and influence processes of designing and implementing socially inclusive approaches towards transformative change in the agricultural sector. To this end, the GENDER Platform has set out key areas of capacity building and strengthening for gender researchers in the CGIAR system and in partner institutes to enable them to enhance their influence and foster institutional culture change towards gender responsive AR4D. The focus on mentoring and leadership development of gender researchers, to support their professional career, personal growth, and capacities, will enable them to increase their perceived legitimacy and relevance – and that of their gender research – to bring gender and social inclusion concerns at the heart of food systems research for development.